Efforts to Improve The Learning Outcomes of Islamic Education Through The Cooperative Imprisonment Model of Students Teams Achievement Division (STAD) - Mochammad Syafiuddin Shobirin; Laila Viki Hildiana (SCHOOLAR: Social and Literature Study in Education, 2021)
This study aims to improve the learning outcomes of grade X students through the cooperative learning model of Student Teams Achievement Division (STAD) in Islamic Religious Education subjects at high school Negeri 1 Jombang. This study uses qualitative research with the research subjects of Islamic Religious Education teachers and grade X students. Prior to the implementation of the Student Teams Achievement Division (STAD) cooperative model, the learning model applied by teachers using lecture methods resulted in students being less active in learning, lack of interaction between students, and less conducive classroom atmosphere. With this problem, the learning results obtained are less than maximum. To improve the learning outcomes of students teachers make efforts in the hope that the learning results obtained maximum results. Based on the results of the study, it is known that in an effort to improve the learning outcomes of grade X students in Islamic Religious Education subjects there is an increase in learning outcomes with the number of students 33 research results obtained with an average of 70.0 with a pre percentage of 33.33% increased to 84.01% with an average of 84. In the implementation of the cooperative learning model Student Teams Achievement Division (STAD) teachers apply 3 stages, namely the planning, implementation and evaluation stages. To find out the results of students' learning is done through pretest and posttest assessment. Based on the results of the study, showed that the model is very effective to improve student learning outcomes through the right Student Teams Achievement Division (STAD) cooperative learning model in Islamic Religious Education subjects because students are easy to accept learning, active in learning, cooperation between students